Program Potensi Desa dan Pengolahan Hasil Bumi Desa Beji, Kapanewon Patuk, Kabupaten Gunung Kidul - Binarti, Floriberta (Jurnal Atma Inovasia, 2023)
Beji Village is one of the villages located in Patuk District, Gunungkidul Regency, the Special Region of Yogyakarta. This paper aims to propose programs to develop the unique potency by using the service method. The village potency consists of the potency of agricultural products such as plantations, agriculture, and tourist attractions. From the results of data collection on the potential of the village, so the author makes an output in the form of an interactive e-book and video that explains the potential of Beji village. In addition, the author also identified the potential and potential of agricultural products as a material for discussion in a pocket book regarding processing agricultural products from mangoes which was then made in the form of an e-book, pocket book and interactive video. Mango fruit is processed into candied fruit which can later provide other options to be used as souvenirs from Beji Village. The results are expected to be useful and become new innovations for Beji Village in developing village innovation.